Constructing polymers towards ultrathin nanosheets with dual mesopores and intrinsic photoactivity. Issue 21 (18th February 2020) - Wen, Yu; Wei, Facai; Xu, Wei; Jiang, Xiaolin; Cui, Jing; Ai, Yan; Chen, Jinming; Cui, Anyang; Hu, Zhigao; Fu, Jianwei; Liu, Shaohua; He, Qingguo; et al.
Abstract : Ultrathin dual-mesoporous conjugated polymer nanosheets were exploited, which exhibited inherent fluorescence-based photoactivity and effective detectability for organophosphates. Abstract : We developed ultrathin dual-mesoporous polymer nanosheets by combining co-assembly of different templates with in situ synthesis of functional polymers, which featured inherent smaller and template-directed larger mesopores (2.6 nm and 15 nm, respectively), ultrathin nanolayers (20 nm), high surface area (268 m 2 g −1 ), intrinsic fluorescent properties and effective detectability for organophosphates.